Hemorrhagic Bronchopneumonia in Adults with Chickenpox. A Case Report - Miguel Ángel Serra Valdés; Gloria Susana Fabra Aguirre; Maury Llana Rodríguez; Yovanis Iser Filtres (Medisur)
Chickenpox is an acute viral infectious disease that is highly contagious and very common in children. When it occurs in adults, age increases severity, with complications that can lead to death in a short period of time. Among the most lethal complications we can find pneumonia and bronchopneumonia, injuries overinfection caused by streptococci and staphylococci with severe sepsis, diverse bleeding, encephalitis, shock, hemorrhagic nephritis with renal failure and necrotizing fasciitis, among others. The case of an 83 years old male patient, with a history of chronic obstructive pulmonary disease and ischemic cerebrovascular atherosclerotic disease that contracted chickenpox and whose evolution was very rapid, with acute respiratory failure and bronchopneumonia massive hemorrhagic shock, to the point of death, is presented. Given the increased incidence of chickenpox, according to reports of the Pedro Kouri Institute of Tropical Medicine, we decided to have this case published.